Global Financial Stability Report, September 2005 : Market Developments and Issues. (Global Financial Stability Report; Global Financial Stability Report ;, 2005)
This paper presents an assessment of the shift in market risks to the household sector, which results from changes in the behavior of financial institutions and from pension reform. It focuses on household saving and asset allocation behavior and analyzes how such behavior may be affected by changes to household risk profiles. It examines the products and services that the financial industry has developed, or may need to develop, to help households meet these new challenges. The paper also discusses possible public policy initiatives on the promotion of a broader range of payout instruments and structures.